Literature-based teaching in the content areas : 40 strategies for K-8 classrooms - Cox, Carole, 1943- (SAGE Publications, 2012)
This guide, packed-full with tools such as mini-lessons technology resources and prompts for discussion, is an indispensible resource when teaching children aged 5 to 14. The literature-based strategies are based in theory and research, as well as being thoroughly classroom-tested.